Spirituality in the Mamongan Tradition for Character Education in Nerangan Hamlet, Mangunrejo Village, Central Java - Siswayanti, Novita (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Mamongan is a Javanese tradition in commemorating the birthday in Javanese calculation of 35 days of selapanan. On the day of selapanan, a child is prayed for by his parents, his hair is shaved and a salvation is held by inviting children aged under five. Mamongan is as a tradition that teaches the values of character education for children in the spiritual implementation of both relationships with God, fellow humans and nature. This study aims to explain the values of spirituality in the mamongan tradition in building character education. This study uses a qualitative descriptive approach with ethnographic methods, namely finding elements of spirituality that are used as a synthesis in character education. The stages in this research are observations on the implementation of the mamongan tradition by interviewing children's parents, community leaders, religious leaders, and cultural experts, which is then followed by a documentation study. Furthermore, the results of the interviews were analyzed. The results of the research on Spirituality in the Mamongan Tradition for Character Education are: 1. Expressions of Gratitude and Prayers of Salvation; 2. Communicating with a culture of smiles, greetings, 3. Tolerance or tepo seliro; 4. Social care; 5. National spirit; 6. Love nature and be environmentally friendly.